Prescribing pattern of Natural Penicillin, Anti- Staphyloccocal Penicillin, Extended-Sprectrum Penicillin in Hospital Sultan Abdul Halim (HSAH) - Mohd Shukri, Mohd Shazwan Hafiz; Aziz, Mohammad Azri; Zainuddin, Siti Sarah; Yahya, Nur Yusrina (2013)
The purpose of this study is to analyze the prescribing pattern of Natural Penicillin, Anti-Staphylococcal Penicillin and Extended-Spectrum Penicillin among physicians in Hospital Sultan Abdul Halim (HSAH) and to determine their conformity with National Antibiotic Guideline 2008. It was a retrospective study involving data obtained from outpatient case notes that were prescribed with penicillin antibiotics during the 6 months period of June to Disember 2012. 50 prescription data from these classes of Penicillin based on each dosage form were collected.The total final data is 450. In this study we excluded any type of Penicillin combined with Clavulanic Acid and Sulbactam. From our result, we found that the trend of use of Natural Penicillins in Hospital Sultan Abdul Halim (HSAH) were more likely for the Upper Respiratory Tract Infection (URTI) 63 (42%) while for Anti-Staphylococcal Penicillins, the antibiotics were in favoured to treat Cellulitis 31 (21%) and abscess 40 (27%). As for Extended-Spectrum Penicillins, the antibiotics were majorly indicated for prophylaxis purpose 98 (66%). The results from this study can be used as surveillance data in order to fight against the resistance of microbials towards Penicillins.